Distribution of Actual Evapotranspiration over Qaidam Basin, an Arid Area in China - Xiaomei Jin (Remote Sensing, 2013)
Evapotranspiration is a major loss flux of the water balance in arid and semi-arid areas. The estimation of actual evapotranspiration has significance for hydrological and environmental purposes. The Surface Energy Balance System (SEBS) algorithm was applied to estimate actual evapotranspiration in the Qaidam Basin and its eight hydrological sub-regions, Northwest China. There were 3,036 cloud-free and atmospherically corrected MODIS satellite images from 2001 to 2011 used in the SEBS algorithm to determine the actual evapotranspiration. The result indicated that the estimated annual actual evapotranspiration of the basin increased with time and the value varied from 72.7 to 182.3 mm. SEBS estimates were 7.5% and 14.1% of observed pan evaporation over the western and eastern areas, respectively. The variation of SEBS actual evapotranspiration is influenced by climate factors, vegetation, net radiation, land cover type and water table depth. The analysis of the evaporative behavior of different land cover types in the basin presented that water bodies, marsh, and farmland had relatively higher mean actual evapotranspiration though these land cover types make up less than 3.5% of the total basin. Bare soil has very low evapotranspiration and covered almost 60% of the study area. The actual evapotranspiration was observed to be decreased with an increase of water table depth. Overall, the SEBS algorithm proved to be useful and has potential for estimating spatial actual evapotranspiration on a regional scale.